2018
DOI: 10.3892/etm.2018.6384
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNAs associated with the mechanical response of hepatic stellate cells by miRNA microarray analysis

Abstract: It has been suggested that hepatic stellate cells (HSCs) could be used in the regulation of liver microcirculation and portal hypertension. The effects of tensile strain on the microRNA (miRNA) profile of HSCs are largely unknown. In this study, we aimed to explore the changes of miRNA expression in tensile strain-treated HSCs. The purity and activation of HSCs were determined by immunofluorescence staining with antibody against desmin and a-SMA, respectively. miRNA profile analysis was performed on HSCs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…The involvement of this c-miRNA in atherosclerosis, which is induced after postprandial lipemia as well as in muscle damage, is intriguing and deserves further investigation. In addition, miR-466b-5p is upregulated under liver disease conditions [42] and is also overexpressed in infection and lipopolysaccharide-induced inflammation [43]. For the other validated miRNAs, there is scarce information with relation to lipid metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…The involvement of this c-miRNA in atherosclerosis, which is induced after postprandial lipemia as well as in muscle damage, is intriguing and deserves further investigation. In addition, miR-466b-5p is upregulated under liver disease conditions [42] and is also overexpressed in infection and lipopolysaccharide-induced inflammation [43]. For the other validated miRNAs, there is scarce information with relation to lipid metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…HL-7702 cells were purchased from cell bank of typical culture preservation committee of chinese academy of Sciences. The cells were cultured at 37˚C in an atmosphere containing 5% CO 2 in Dulbecco's modified Eagle's medium (DMEM; Jiangsu Kaiji Biotechnology co., ltd.) containing 10% fetal bovine serum (FBS; Gibco; Thermo Fisher Scientific, Inc.) for different durations (2,6,12,24 and 48 h). The cell line was authenticated by short tandem repeat analysis.…”
Section: Methodsmentioning
confidence: 99%
“…cirrhosis of the liver can lead to sinusoidal portal hypertension, in which the pressure in the hepatic portal vein increases, which can cause these veins to become significantly dilated (5). Hepatocytes are epithelial cells that line the sinusoids, which are directly and indirectly affected by biomechanical factors, such as the pressure of the hepatic portal vein and the tension strain after the dilation of hepatic sinusoids (6). a number of studies have shown the important roles of biomechanical factors in the regulation of hepatocyte function.…”
Section: Introductionmentioning
confidence: 99%
“…7 Additionally, through an investigation on the mechanisms of miRNA profile in hematopoietic stem cells (HSCs), one team found that rno-miR-125b-2-3p was downregulated after tensile strain was applied to activated HSCs. 8 In light of a previous study, we developed and verified a novel classifier based on two miRNAs, miR-933 and miR-125b-2-3p. They are capable of predicting disease progression and the benefit of receiving standard first-line chemotherapy in advanced CRC.…”
Section: Introductionmentioning
confidence: 98%
“…In recent studies, hsa‐miR‐125b‐2‐3p was found to be linked with the pathological stage of CRC 7 . Additionally, through an investigation on the mechanisms of miRNA profile in hematopoietic stem cells (HSCs), one team found that rno‐miR‐125b‐2‐3p was downregulated after tensile strain was applied to activated HSCs 8 . In light of a previous study, we developed and verified a novel classifier based on two miRNAs, miR‐933 and miR‐125b‐2‐3p.…”
Section: Introductionmentioning
confidence: 99%